The Facial Aesthetic index: An additional tool for assessing treatment need - Shobha Sundareswaran; Ranjith Ramakrishnan (Wolters Kluwer Medknow Publications, 2016)
Objectives: Facial Aesthetics, a major consideration in orthodontic diagnosis and treatment planning, may not be judged correctly and completely by simply analyzing dental occlusion or osseous structures. Despite this importance, there is no index to guarantee availability of treatment or prioritize patients based on their soft tissue treatment needs. Individuals having well-aligned teeth but unaesthetic convex profiles do not get included for treatment as per current malocclusion indices. The aim of this investigation is to develop an aesthetic index based on facial profiles which could be used as an additional tool with malocclusion indices. Materials and Methods: A chart showing typical facial profile changes due to underlying malocclusions was generated by soft tissue manipulations of standardized profile photographs of a well-balanced male and female face. A panel of 62 orthodontists judged the profile photographs of 100 patients with different soft tissue patterns for assessing profile variations and treatment need. The index was later tested in a cross-section of school population. Statistical analysis was done using "irr" package of R environment version 2.15.1. Results: The index exhibited very good reliability in determining profile variations (Fleiss kappa 0.866, P < 0.001), excellent reproducibility (kappa 0.9078), high sensitivity, and specificity (95.7%). Testing in population yielded excellent agreement among orthodontists (kappa 0.9286). Conclusions: A new Facial Aesthetic index, based on patient's soft tissue profile requirements is proposed, which can complement existing indices to ensure treatment to those in need.